2022
DOI: 10.1111/lam.13684
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial activity and mechanism of chloroform fraction from aqueous extract of mugwort leaves (Artemisia argyi L.) against Staphylococcus aureus

Abstract: In this work, the antibacterial activity and mechanism of chloroform fraction obtained from aqueous extract of mugwort leaves against Staphylococcus aureus were investigated. The extract showed obvious antibacterial activity against S. aureus which the minimum inhibitory concentration and minimum bactericidal concentration were determined to be 3·0 and 6·0 mg ml−1 respectively. The mechanism study suggested that the extract could destroy the integrity of the S. aureus cell walls and increase the permeability o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 16 publications
0
11
0
Order By: Relevance
“…Although the bioactive ingredients of A. argyi exhibit various pharmacological and therapeutic functions, few studies have investigated the anti-infectious diseases of A. argyi [ 11 , 12 ]. We presented here that AEE inhibits HSV-1 and HSV-2 infection and exerts inhibitory function against ACV-resistant HSV-1 strains, implying a novel antiviral mechanism different from ACV.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although the bioactive ingredients of A. argyi exhibit various pharmacological and therapeutic functions, few studies have investigated the anti-infectious diseases of A. argyi [ 11 , 12 ]. We presented here that AEE inhibits HSV-1 and HSV-2 infection and exerts inhibitory function against ACV-resistant HSV-1 strains, implying a novel antiviral mechanism different from ACV.…”
Section: Discussionmentioning
confidence: 99%
“…A. argyi has been historically used to warm menstruation, relieve pain, disperse dampness and cold, and regulate Qi and blood. Up to now, several volatile oils, terpenoids, flavonoids, alkaloids, and polysaccharides have been isolated from A. argyi extract, which demonstrates antioxidative [ 7 ], anti-cancer [ 8 , 9 ], anti-inflammatory [ 10 ], antibacterial [ 11 , 12 ] and immunosuppressive [ 13 ] effects. Notably, most studies focus on the aqueous extract and essential oil component of A. argyi .…”
Section: Introductionmentioning
confidence: 99%
“…In order to slow down or repress the evolution of bacterial resistance, the development of new antibacterial Chinese herbal medicines and their preparations have become an important hotspot in the field of antibacterial drug research and development. For example, Zhang et al [ 27 ] found that the aqueous extract of Artemisia argyi leaves could destroy the integrity of the cell wall of S. aureus and increase the permeability of the cell membrane at a certain concentration, but it could not kill S. aureus in a short time; Zhou et al [ 28 ] found that a part of n-butanol and ethanol crude extract of the Dendrobium shell had strong antibacterial activity against Salmonella paratyphimurium and S. aureus , and the antibacterial mechanism might be related to the synthesis inhabitation of bacterial proteins. However, both Chinese herbal compound preparations and single Chinese herbal medicines all have complex chemical components, leading to unclear antibacterial mechanisms and lack of standard drug use specifications.…”
Section: Discussionmentioning
confidence: 99%
“…Outbreaks of food poisoning events due to microbes tend to increase in recent years. Among them, Staphylococcus aureus ( S. aureus ) accounts for 25% of the total, and it is the third largest microbial pathogen after Haemophilus parahaemolyticus and Salmonella [ 1 ]. As a common foodborne pathogen, S. aureus can grow in a wide range of temperatures and pH.…”
Section: Introductionmentioning
confidence: 99%